Recent advances in positron emission tomography for detecting early fibrosis after myocardial infarction - Wu, Qiuyan; Song, Jialin; Liu, Wenyan; Li, Li; Li, Sijin (Frontiers in Cardiovascular Medicine, 2024)
Cardiac remodeling after myocardial infarction is one of the key factors affecting patient prognosis. Myocardial fibrosis is an important pathological link of adverse ventricular remodeling after myocardial infarction, and early fibrosis is reversible. Timely detection and intervention can effectively prevent its progression to irreversible ventricular remodeling. Although imaging modalities such as CMR and echocardiography can identify fibrosis, their sensitivity and specificity are limited, and they cannot detect early fibrosis or its activity level. Positron emission tomography (PET) allows non-invasive visualization of cellular and subcellular processes and can monitor and quantify molecules and proteins in the fibrotic pathway. It is valuable in assessing the extent of early myocardial fibrosis progression, selecting appropriate treatments, evaluating response to therapy, and determining the prognosis. In this article, we present a brief overview of mechanisms underlying myocardial fibrosis following myocardial infarction and several routine imaging techniques currently available for assessing fibrosis. Then, we focus on the application of PET molecular imaging in detecting fibrosis after myocardial infarction.